Structural proteins of human coronaviruses: what makes them different? - Minigulov, Nail; Boranbayev, Kuandyk; Bekbossynova, Ayaulym; Gadilgereyeva, Bakhytgul; Filchakova, Olena (Frontiers in Cellular and Infection Microbiology, 2024)
Following COVID-19 outbreak with its unprecedented effect on the entire world, the interest to the coronaviruses increased. The causative agent of the COVID-19, severe acute respiratory syndrome coronavirus – 2 (SARS-CoV-2) is one of seven coronaviruses that is pathogenic to humans. Others include SARS-CoV, MERS-CoV, HCoV-HKU1, HCoV-OC43, HCoV-NL63 and HCoV-229E. The viruses differ in their pathogenicity. SARS-CoV, MERS-CoV, and SARS-CoV-2 are capable to spread rapidly and cause epidemic, while HCoV-HKU1, HCoV-OC43, HCoV-NL63 and HCoV-229E cause mild respiratory disease. The difference in the viral behavior is due to structural and functional differences. All seven human coronaviruses possess four structural proteins: spike, envelope, membrane, and nucleocapsid. Spike protein with its receptor binding domain is crucial for the entry to the host cell, where different receptors on the host cell are recruited by different viruses. Envelope protein plays important role in viral assembly, and following cellular entry, contributes to immune response. Membrane protein is an abundant viral protein, contributing to the assembly and pathogenicity of the virus. Nucleocapsid protein encompasses the viral RNA into ribonucleocapsid, playing important role in viral replication. The present review provides detailed summary of structural and functional characteristics of structural proteins from seven human coronaviruses, and could serve as a practical reference when pathogenic human coronaviruses are compared, and novel treatments are proposed.